Pengujian Angka Lempeng Total (ALT) Pada Ikan Tongkol (Euthynnus Affinis) Di Stasiun Karantina Ikan Pengendalian Mutu Dan Keamanan Hasil Perikanan Aceh - Gebrina Reski; Anhar Rozi; Afdhal Fuadi (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Indonesia is a maritime country with abundant fishery and marine products. Indonesian fishery products in 2015 reached 14.79 tonnes. Tuna (Euthynnus affinis) is one of the most important pelagic fish species found in Indo-Pacific waters living in the neritic area. Its geographical distribution includes the Indian Ocean and the Pacific Ocean. The results of the ALT test on tuna obtained a variety of colony counts. This research uses a descriptive method. Descriptive, namely research conducted to determine the value of a characteristic or number, either one characteristic or more without making comparisons, to relate it to other quantities. Research is conducted with the main objective of making a picture of a situation objectively (actual situation). Tuna taken from 3 different traders obtained the ALT value of sample A1 which was 2.6 x 104/gr, sample A2 which was 2.4 x 104/gr, and sample A3 which was 4.0 x 103/gr for 48 hours with temperature 350o C. After testing it can be concluded that the total plate number (ALT) of bacteria found in tuna is in accordance with the SNI 2332.3: 2015 standard concerning tuna ALT, which is 106.